Safety and Efficacy of Risankizumab in the Treatment of Chronic Plaque-Type Psoriasis: A Pilot Single-Arm, Single-Center, Prospective Cohort Study (Bangladesh Armed Forces Medical Journal, 2025)
Background: Chronic plaque-type psoriasis is a prevalent autoimmune disease characterized by sharply demarcated erythematous plaques and significantly impacts patients' quality of life (QoL). Conventional treatments often fail, leading to the need for effective alternatives. Risankizumab, a humanized monoclonal antibody, has emerged as a promising treatment option in recent years, demonstrating safety and efficacy. Objective: This prospective cohort study evaluates the clinical efficacy and safety of Risankizumab in treating moderate to severe chronic plaque-type psoriasis. Methods: Conducted at Sheikh Jaber Al-Ahmad Armed Forces Hospital in Kuwait from November 2021 to October 2023, this study involved 10 patients of moderate to severe chronic plaque-type psoriasis, excluding pregnant and lactating women and individuals under 18. Data were collected using a structured questionnaire, and clinical follow-ups were done at 3, 6, 12, and 24 months to evaluate efficacy and safety. Results: The study's participants were predominantly male (90%) with a median age of 34 years. After 24 months of continuous Risankizumab treatment, 70% achieved PASI 90, 20% achieved PASI 75, and 10% achieved PASI 100. Additionally, 90% achieved sPGA 0/1, and 90% achieved DLQI 0/1. The body surface area (BSA) of affected regions saw a significant improvement, with an average decrease of nearly 97% from baseline. Adverse events were infrequent; one patient experienced latent tuberculosis, leading to treatment discontinuation, while another had transient pancytopenia that resolved on follow-up. Conclusion: Risankizumab is seen as highly effective and safe biologics in the treatment of moderate to severe chronic plaque-type psoriasis, demonstrating substantial improvement in clinical severity and QoL over a 24-month period.Bangladesh Armed Forces Med J Vol 58 No (1) June 2025, pp 22-29